EPIDEMIOLOGICAL PROFILE OF ELDERLY VICTIMS OF DOMESTIC VIOLENCE IN DIFFERENT BRAZILIAN REGIONS (CIPEEX, 2022)
THE PRESENT STUDY SEEKS TO ADDRESS A REALITY THAT IS INCREASINGLY EVIDENT IN THE GLOBAL CONTEXT, IN WHICH AGING IS GAINING MORE SPACE AND PARTICIPATION IN EPIDEMIOLOGICAL INDICATORS. SINCE LIFE EXPECTANCY, MAINLY IN DEVELOPED AND DEVELOPING COUNTRIES, SUCH AS BRAZIL, HAS BEEN EXPANDING, POPULATION GROWTH HAS BEEN NOTABLY ASSOCIATED WITH THE VIOLENCE PERPETRATED AGAINST SENIOR CITIZENS, CHARACTERIZING WHAT IS KNOWN AS €ŒVIOLENCE AGAINST THE ELDERLY€, WHICH INVOLVES ACTS THAT CULMINATE IN THE LOSS OF THEIR QUALITY OF LIFE. DUE TO THE TERRITORIAL AND CULTURAL EXTENSION OF BRAZIL, IT IS EXPECTED THAT THERE WILL BE DIFFERENT EPIDEMIOLOGICAL PROFILES IN EACH REGION WITH REGARD TO THE VIOLENCE AGAINST THE ELDERLY. THE STUDY CONSISTS OF AN INTEGRATIVE LITERATURE REVIEW THAT AIMED TO ANALYZE AND COMPARE DATA RELATED TO DOMESTIC VIOLENCE AGAINST THE ELDERLY IN DIFFERENT BRAZILIAN REGIONS, EMPHASIZING THE EPIDEMIOLOGY RELATED TO THE THEME. FOR THE METHODS, A BIBLIOGRAPHICAL SURVEY WAS CARRIED OUT FROM ARTICLES SEARCHED IN THE FOLLOWING DATABASES: BRASIL SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO), LITERATURA LATINO-AMERICANA E DO CARIBE EM CINCIAS DA SAÚDE (LILACS) AND COORDENAO DE APERFEIOAMENTO DE PESSOAL DE NVEL SUPERIOR (CAPES). AS INCLUSION CRITERIA, COMPLETE, AVAILABLE FOR FREE AND ORIGINAL ARTICLES WERE CONSIDERED. ALSO THOSE WHICH ADDRESSED THE BRAZILIAN REGIONS, PUBLISHED IN THE LAST 5 YEARS, AND EXCLUDING NON-BRAZILIAN ARTICLES, BIBLIOGRAPHIC REVIEWS, ABSTRACTS, META-ANALYSES, DUPLICATE ARTICLES AND OTHERS THAT DID NOT MEET THE ESTABLISHED GUIDING QUESTION. REGARDING THE RESULTS, 20 ARTICLES THAT MET THE PROPOSED DEMANDS WERE CHOSEN. THROUGH DATA ANALYSIS, IT WAS POSSIBLE TO CORRELATE THE REGIONS STUDIED WITH THE EPIDEMIOLOGICAL PROFILE OF THE VICTIMS AND CONCLUDE THAT THERE IS A PATTERN OF CHARACTERISTICS RELATED TO SOCIAL AND ECONOMIC ASPECTS, CONSIDERING AGE GROUP, RACE AND GENDER, IN ADDITION TO THE TYPES OF VIOLENCE OBSERVED. IN CONCLUSION, IT IS POSSIBLE TO STATE THAT BRAZIL, DESPITE BEING A COUNTRY OF CONTINENTAL DIMENSIONS AND HAVING REGIONS WITH VERY VARIED AND DIVERSE CULTURES, HAS SEVERAL COMMON CRITERIA IN TERMS OF THE EPIDEMIOLOGICAL PROFILE OF ELDERLY VICTIMS OF DOMESTIC VIOLENCE.
Keywords: abuso de idosos; epidemiologia; violência doméstica